Effects of green mining practices on corporate sustainable development: role of green innovation, green organizational commitment, and corporate social responsibility - Jianchun, Yu (Frontiers in Environmental Science, 2024)
BackgroundChina is the top global consumer, importer, and producer of coal, accounting for about half of the world’s totals. Yet despite all this progress in renewable energy, coal still provided 56 percent of China’s energy consumption, and the country has the fourth-largest reserve globally. However, coal mining also releases enormous amounts of methane, a very potent greenhouse gas. Additionally, it contributes over 70% to the total CO2 within the country.PurposeThis study evaluates the effect of green mining practices on green innovation, employee green organizational commitment, and corporate sustainable development in the mining industry of China.MethodologyThe data was collected through an online survey and distributed all over China. For this research, 511 responses were analyzed using SmartPLS 4.1.ResultsThe results indicate that green marketing practices have a direct positive and significant effect on green innovation (β = 0.493), organizational commitment (β = 0.476), and organizational sustainable development (β = 0.0.195). The study proves that green innovation significantly affects both organizations’ sustainable development (β = 0.262) and their commitment (β = 0.0.293). Additionally, green innovation and organizational commitment significantly mediate the relationship between green marketing practices and corporate sustainable development. Moreover, the study observed that corporate social responsibility significantly moderated the influence of green mining practices on green innovation, organizational commitment, and corporate sustainable development. Cumulatively green mining practices, direct and indirect effects of green innovation and organizational commitment, and moderation of corporate social responsibility explained 67.2% variance in the corporate sustainable development.ConclusionThe study results further attest that green practices and corporate social responsibility play an essential role in underpinning sustainability and innovation in the mining sector. They also provide important lessons for policymakers and other industrial stakeholders on improving sustainable development.